1991
DOI: 10.1093/carcin/12.7.1193
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin and rutin as inhibitors of azoxymethanol-induced colonic neoplasia

Abstract: Dietary quercetin (QU) and rutin (RU), phenolic flavonoids commonly found in many fruits and vegetables, were provided to CF1 female mice for 50 weeks to assess the ability of these compounds to inhibit azoxymethanol (AOM)-induced colonic neoplasia. In addition to a control group fed an AIN 76A diet, five other groups received that diet to which was added either 0.1, 0.5 or 2.0% QU and 1.0 or 4.0% RU. Acute studies revealed that, among saline controls, no alteration of any proliferative parameters of colonic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
169
0
4

Year Published

1995
1995
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 413 publications
(177 citation statements)
references
References 0 publications
2
169
0
4
Order By: Relevance
“…Recently, several flavonoids, such as quercetin and genistein, and isothiocyanates have inhibited tumor growth and induced apoptosis in cancer cells by interrupting cell cycle progression in the G 2 /M phase. [33][34][35][36][37] It is also known that the Cdc2/ cyclin B1 kinase complex is a known regulator of the G 2 /M transition. 38,39 The Cdc2 activity is significantly reduced and decreases the interaction with cyclin B1 for the exit from mitosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several flavonoids, such as quercetin and genistein, and isothiocyanates have inhibited tumor growth and induced apoptosis in cancer cells by interrupting cell cycle progression in the G 2 /M phase. [33][34][35][36][37] It is also known that the Cdc2/ cyclin B1 kinase complex is a known regulator of the G 2 /M transition. 38,39 The Cdc2 activity is significantly reduced and decreases the interaction with cyclin B1 for the exit from mitosis.…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin has anti-inflammatory and antioxidant effects and act as a immunomodulator [58]. A diet rich in quercetin has been reported to inhibit the development of carcinogeninduced rat mammary cancer [59], colonic neoplasia [60], oral carcinogenesis [61], and skin tumor formation in three models of skin carcinogenesis in mice when administered by topical application [62]. Quercetin may account for the beneficial effects of dietary fruits and vegetables on mutagens and carcinogens, including metals [63].…”
Section: Phytochemicals Skin Cancer and Rosmentioning
confidence: 99%
“…Their results showed that flavonols exhibit distinctive antioxidant and anti-inflammatory potentials and that the structures, required to strengthen these activities, vary with sorts of free radicals and mechanisms. Quercetin blocked the aggregation of human platelets by ADP and thrombin, and this compound has gained considerable prominence as an inhibitor of carcinogens and of cancer cell growth in many experimental and human tumors [27,28].…”
Section: Introductionmentioning
confidence: 99%